OS INTERESSES COLETIVOS DE PROTEÇÃO AMBIENTAL E URBANÍSTICA E O SISTEMA DE JUSTIÇA NO MARANHÃO: a atuação do Poder Judiciário e do Ministério Público no período de 2015 a 2020 - MARTINI, Letícia Moreira de (2021)
The theme of this dissertation is the judicialization of collective interests. The delimitation of the theme and the demarcation of the research object restricted the analysis over the performance of the Judiciary and the Public Prosecutor’s Office of Maranhão in the area of environmental and urban protection in the period from 2015 to 2020. The reflections on this theme faced the dilemmas about the expansion of the justice system over the administrative sphere, especially considering the limits and effectiveness of judicial action. In addition to bibliographic research, especially focused on reflections around the two theoretical frameworks (judicial expansion and collective interests), a documentary research was used to assess the measures of action, both judicial and extrajudicial, of the Judiciary and the State Public Prosecutor’s Office institutions, in the first degree of jurisdiction, subscribed by the Court of Diffuse and Collective Interests of São Luís, by the 7th and 8th Specialized Public Prosecutor’s Offices and by the Operational Support Center for the Environment, Urbanism and Cultural Heritage. For this, the strategies and the arguments presented by the plaintiffs were considered, present in the collective actions selected through the hypothetical-deductive method developed by Karl R. Popper, and systematically categorized in accordance with the techniques that guide the content analysis, for then, using a descriptive procedure method, develop data analysis, enabling the exposure of results. Public reports on the activities of the Maranhão Public Prosecutor’s Office from 2015 to 2019 were also analyzed. The initial theoretical discussion developed from the understanding of the expansion of the justice system in Brazil, made visible in the cove of a democratic political project, which housed a broad concept of access to justice, all under the canopy of a socially biased state and the birth of collective interests constitutionally positivized, legally claimable on a comprehensive scale when not offered in its ordinary sphere. This judicial expansion was accompanied by a greater hermeneutical scope and consequent creative freedom, whose argumentative limits lack rational weights capable of rebalancing the federative costume, which may come to function as potential differentiators of the concepts of judicialization and activism. On the other hand, the massive accommodation of interests arising from increasingly complex of social standards, made possible a turnaround in traditional procedural techniques, encouraging the raising of typical values of a collective microsystem, which started to have the Public Prosecutor’s Office as the main inducing agent, mainly due to its new constitutional profile, which also resulted in its potential for resolution through extrajudicial instruments. All this expansionist dynamics gave rise to discussions about the limits imposed on jurisdictional interference in the administrative sphere, whose goals emerge as real challenges in the face of actions that resist the negotiated resolution proposition, and which evidently led to doubts about the effectiveness of the Justice System of the State of Maranhão in the protection of collective interests to the environment and to the urban order.